The Detection of Silent Celiac Disease In patients With Type 1 Diabetes Mellitus by the use of Anti Tissue Transglutaminase Antibodies - Obaid, Anower Tuama; Kubba, Rushdi A.H.; Al Hergani, Zaidan K. (AL-Kindy College Medical Journal, 2012)
Objective: Detection the presumptive prevalence of silent celiac disease in patients with type 1 diabetes mellitus with determination of which gender more likely to be affected.Methods: One hundred twenty asymptomatic patients [75 male , 45 female] with type 1 diabetes mellitus with mean age ± SD of 11.25 ± 2.85 year where included in the study . All subjects were serologically screened for the presence of anti-tissue transglutaminase IgA antibodies (anti-tTG antibodies) by Enzyme-Linked Immunosorbent Assay (ELISA) & total IgA was also measured for all using radial immunodiffusion plate . Anti-tissue transglutaminase IgG was selectively done for patients who were expressing negative anti-tissue transglutaminase IgA with low total IgA levels & results were compared to that obtained from healthy 60 persons with mean age ± SD for them was 15.25 ± 3.85 year . Al - Kindy Col Med J 2012 ; Vol .8 No. (2) p: 132Results : Fourteen out of one hundred twenty (11.66 % ) diabetic patients had expressed positivity to anti-tissue transglutaminase IgA compared to 1/60 ( 1.66 %) of non diabetic patients who had expressed such positivity , P value equals to 0.0221 & it is considered to be statistically significant. Three out of one hundred twenty (2.5 % ) diabetic patients had expressed total IgA deficiency whereas all of non diabetic patients were expressing total IgA within the normal range , P value equals to 0.55 & it is considered to be not statistically significant. All of three diabetic patients with total IgA deficiency were not showing positivity to anti-tissue transglutaminase IgG . Six mals & Eight female of those with type 1 diabetes mellitus had expressed positivity to anti-tissue transglutaminase IgA , P value equals to 0.1426 & it is considered to be not statistically significant .Conclusion : There is an increased prevalence of IgA antitissue transglutaminase antibodies ( 11.66 % ) in children & adolescent with type 1 diabetes mellitus in comparison with control group.